A Systematic Review of Epidemiological characteristics, routine laboratory diagnosis, clinical signs and risk factors for hand, foot and mouth disease - Angela; Josephine (International Medical Journal Corp. Ltd, 2024)
Background: Hand, foot and mouth disease (HFMD) is a common, mild viral infection that mostly affects children under 5 years of age. The causative agent is typically enterovirus A (EV-A), which includes the serotypes Coxsackievirus A and enterovirus A71, A76, and A89–92; serotypes of enterovirus B are sometimes detected. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The detection of clinical risk factors and the temporal, spatial and socio-demographic distribution epidemiological characteristics of severe HFMD contribute to the timely diagnosis and intervention, the results of this study can be the reference of further clinical and public health practice.